The Sources of Organic Carbon in the Deepest Ocean: Implication From Bacterial Membrane Lipids in the Mariana Trench Zone - Li, Jiwei; Chen, Zhiyan; Li, Xinxin; Chen, Shun; Xu, Hengchao; Ta, Kaiwen; Dasgupta, Shamik; Bai, Shijie; Du, Mengran; Liu, Shuangquan; Peng, Xiaotong (Frontiers in Earth Science, 2021)
Hadal trenches have higher microbial carbon turnover rates as compared to adjacent abyssal plains. However, the source of organic carbon in the trench remains enigmatic. In this study, we show that a fraction of organic carbon is possibly derived in-situ and correlated with chemoautotrophic communities supported by the fluid discharge of water-rock interaction in the trench wall, based on analysis of glycerol dialkyl glycerol tetraether (GDGT) membrane lipids, including archaeal isoprenoid GDGTs (IsoGDGTs) and bacterial branched GDGTs (BrGDGTs), in sediments and rocks of the Mariana and Yap Trenches, northwest Pacific Ocean. These trench sediments contained relative higher BrGDGTs ratios, which was a rare observation in the open ocean. The BrGDGT-to-IsoGDGT ratios ranged in 0.02–0.88 (mean=0.10±0.11) in sediments and 0.09–0.38 (mean=0.17±0.13) in altered rocks. The calculated values of branched and isoprenoid tetraether (BIT) index ranged from 0.02–0.73 (mean=0.18±0.11) in sediments and from 0.16–0.9 in altered rocks (mean=0.37±0.27). Moreover, these GDGTs exhibited similar characteristics to those of altered basalt rocks, indicating inputs of organic carbon from the trench subsurface environment. Thus, in addition to organic-rich material settling, we propose chemoautotrophic activity in oceanic crust could be an additional source of organic carbon in the deepest part of the ocean, with an important role in deep-sea carbon cycles.